Adolescent women can perform a point-of-care test for trichomoniasis as accurately as clinicians. Issue 7 (30th June 2010) - Huppert, Jill S; Hesse, Elizabeth; Kim, Grace; Kim, Michael; Agreda, Patricia; Quinn, Nicole; Gaydos, Charlotte
Abstract : Objectives: To compare the accuracy (ie, correlation, sensitivity, specificity) of self-performed point-of-care (POC) tests with clinician-performed tests for trichomoniasis in adolescent women. Methods: Sexually experienced women aged 14–22 years (n=209) collected a vaginal swab and performed a POC test for trichomoniasis. Using a speculum, the clinician obtained vaginal swabs that were tested for trichomoniasis using the POC test, wet mount, culture and transcription-mediated amplification (TMA) using standard and alternative primers. Self and clinician results were compared with true positives, defined as either culture-positive or TMA-positive with both sets of primers. Results: Participants' mean age was 17.8 years; 87% were African-American; 74% reported vaginal itching or discharge and 51 (24%) had trichomoniasis. Over 99% correctly performed and interpreted her self-test. Self and clinician POC tests were highly correlated (95.7% agreement, κ 0.87). Compared with true positives, the sensitivity of the self-POC test was 78% (CI 65% to 89%), similar to that of the clinician-POC test (84%, CI 71% to 93%) and culture (82%, CI 69% to 92%), and significantly better than wet mount (39%, CI 26% to 54%). The specificity of the self-POC test was 99% (CI 96% to 100%), similar to that of the clinician-POC test (100%, CI 98% to 100%). The sensitivity of the self-POC test was not affected by vaginal symptoms or other variables. Conclusions: Young women performing a self-POC test detected as many trichomoniasis infections as clinician-POC tests or culture, twice as many as wet mount and slightly fewer than an amplified test. Incorporating self-obtained or self-performed POC tests into routine practice could effectively increase the identification and treatment of trichomoniasis in this vulnerable population.